2017
DOI: 10.1002/ptr.5777
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone Inhibits STAT3 Signaling to Alleviate Cardiac Fibrosis in Type 1-like Diabetic Rats

Abstract: Cryptotanshinone is an active principal ingredient isolated from Salvia miltiorrhiza (Danshen), a medicinal plant used in China to treat cardiac disorders. The objective of this study was to investigate the effect of cryptotanshinone on myocardial fibrosis in diabetic rats. In streptozotocin-induced type 1 diabetic model hyperglycemic rats (STZ-treated rats), fasting blood glucose levels and heart weight/body weight ratio were markedly increased but both were not modified by cryptotanshinone. Additionally, car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…Recently, researchers found more biofunctions of CTS. For example, CTS alleviated cardiac fibrosis in type 1‐like diabetic rats . In addition, CTS ameliorated synovitis and prevented joint damage of rats with type 2 collagen‐induced arthritis .…”
Section: Discussionmentioning
confidence: 97%
“…Recently, researchers found more biofunctions of CTS. For example, CTS alleviated cardiac fibrosis in type 1‐like diabetic rats . In addition, CTS ameliorated synovitis and prevented joint damage of rats with type 2 collagen‐induced arthritis .…”
Section: Discussionmentioning
confidence: 97%
“…Among all these factors, myocardial fibrosis is the most frequently proposed mechanism to explain cardiac changes in DCM. Many studies have shown that inhibiting myocardial fibrosis can attenuate the progress of DCM in animal experiments (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Cryptotanshinone is an active principal ingredient isolated from Salvia miltiorrhiza (Danshen). Oral administration of 10 mg/kg/d cryptotanshinone for 28 days attenuates the cardiac fibrosis in STZ-induced diabetic rats by inhibiting STAT3 pathway and MMP-9 expression [ 87 ].…”
Section: Herbal Medicines: Promising Therapeutic For Dcmmentioning
confidence: 99%